PENGARUH MODEL TREASURE HUNT TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA SD - Adisti, Nurul; Waldi, Atri; Ladiva, Hasmai Bungsu; Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Treasure Hunt learning model on the learning outcomes of second-grade elementary school students in Pancasila Education, focusing on the competency of caring for the environment. A quantitative approach with a Quasi-Experimental method and a Nonequivalent Control Group Design was used, involving two intact classes (a control class and an experimental class) at SDN 05 Surabayo, each consisting of 22 students. Data were collected through a validated and reliable multiple-choice test (Cronbach's Alpha = 0.746) administered as a pretest and posttest, along with attitude and skill assessment sheets. Descriptive analysis showed that the mean posttest score of the experimental class (75.91) was higher than that of the control class (66.82). A paired sample t-test indicated a significant improvement in both the control (t = -3.930, p < 0.001) and experimental (t = -6.796, p < 0.001) classes. However, an independent sample t-test comparing the posttest scores of both classes showed no statistically significant difference (t = -1.973, p = 0.055), meaning the null hypothesis was accepted. Despite this, students in the experimental class displayed markedly higher enthusiasm, engagement, and motivation during the game-based learning stages. These findings suggest that while the Treasure Hunt model enhances classroom engagement, its statistical superiority over conventional instruction was not confirmed in this single-session implementation.